For what it's worth: European Arts & humanities graduates' employability and their engagement in society. (April 2023) - Comunian, Roberta; Jewell, Sarah; Sunmoni, Adesola; Dent, Tamsyn
How do European Arts and Humanities (A&H) graduates contribute to their economies and societies? This paper aims to answer this challenging research question by analysing data from the 2018 pilot Eurograduate survey of graduates. The article explores the monitoring of employment dynamics and considers the labour market outcomes of A&H graduates compared to other graduate groups. Our analysis enables an understanding of the utilisation of A&H graduates' knowledge and skills in the current employment market (job-qualification match) and more specifically, their contribution to legal, social and cultural occupations. The dataset variables enable an exploration of the multiple contributions made by A&H graduates to other aspects of contemporary society. Specifically, we examine graduates' volunteering activity during and after their degree, alongside other forms of civic engagement, including political and social action. The findings contribute to the broader debate on the value and impact of A&H degrees beyond measurements of graduate earnings.